1984
DOI: 10.1017/s0043174500059798
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Response of Two Foxtail (Setaria) Species to Diclofop

Abstract: ED50values (the dosage required to reduce the posttreatment gain in dry weight by 50%) for diclofop applied to green and yellow foxtail [Setaria viridis(L.) Beauv. ♯3SETVI andS. lutescens(Weigel.) Hubb. ♯ SETLU] at the two- and four-leaf stages were calculated from linear regression equations derived by plotting the logarithm of the applied dosage against the relative growth reduction expressed as a probit value. At the two-leaf stage, green foxtail was more susceptible to the chemical than yellow foxtail but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Miller and Alley (1987) made a similar observation, noting that increased herbicide rates were required to achieve comparable control when applied at later growth stages. Similar responses have been observed with cyclohexendione and aryloxyphenoxy propionate herbicides (Harker and Blackshaw 1991;Klingaman et al 1991;Morrison and Maurice 1984;Schreiber et al 1979;Todd and Stobbe 1977).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Miller and Alley (1987) made a similar observation, noting that increased herbicide rates were required to achieve comparable control when applied at later growth stages. Similar responses have been observed with cyclohexendione and aryloxyphenoxy propionate herbicides (Harker and Blackshaw 1991;Klingaman et al 1991;Morrison and Maurice 1984;Schreiber et al 1979;Todd and Stobbe 1977).…”
Section: Introductionsupporting
confidence: 77%
“…The lack of a direct relationship between herbicide efficacy and wild oat growth stage indicates that other factors may overshadow growth stage as a determinant of herbicide efficacy. Although several studies have demonstrated the importance of weed growth stage on imazamethabenz and diclofop performance (Harker and O'Sullivan 1991;Miller and Alley 1987;Morrison and Maurice 1984;Schreiber et al 1979;Todd and Stobbe 1977), these results indicate that environmental conditions and weed demographics may be equally important.…”
Section: Resultsmentioning
confidence: 84%
“…Weed growth stage can have an impact on the efficacy of annual grass herbicides used in cereals (Blackshaw and Harker 1996). Diclofop was more effective on green foxtail (Setaria viridis L.) when applied at an early growth stage (Morrison and Maurice 1984). Similarly, imazamethabenz was more effective on wild oat (Avena fatua L.) when applied at early growth stages (Harker and O'Sullivan 1991;Pillmoor and Caseley 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Single applications of imazamox at either 36 or 54 g/ha controlled Italian ryegrass better when applied POST1 than POST2 because of weed size at herbicide application; however, control from these treatments was no more than 68% 150 DAE (Table 2). Weed growth stage can influence the efficacy of annual grass herbicides used in cereals (Blackshaw and Harker 1996;Harker and O'Sullivan 1991;Morrison and Maurice 1984). Imazamox at 54 g/ha controlled more Italian ryegrass than imazamox at 36 g/ha at both the POST1 and POST2 timings.…”
Section: Resultsmentioning
confidence: 99%